2021
DOI: 10.1007/s12195-021-00672-1
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Influence of Viscoelastic and Adhesive Cues on Fibroblast Spreading and Focal Adhesion Organization

Abstract: Tissue fibrosis is characterized by progressive extracellular matrix (ECM) stiffening and loss of viscoelasticity that ultimately results in reduced organ functionality. Cells bind to the ECM through integrins, where av integrin engagement in particular has been correlated with fibroblast activation into contractile myofibroblasts that drive fibrosis progression. There is a significant unmet need for in vitro hydrogel systems that deconstruct the complexity of native tissues to better understand the individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 91 publications
1
24
1
Order By: Relevance
“…Despite the simplistic view that soft microenvironments are necessary to reduce scar formation, as in fetal wound healing, the increased signaling and cytoskeletal remodeling on HA gels indicate the importance of the modulation of contractile machinery of fibroblasts in wound repair, as discussed earlier in this section. Further investigation of this phenomenon via studies that take HA viscoelastic substrates into account is also warranted ( 210 ).…”
Section: Repair and Fibroblastsmentioning
confidence: 99%
“…Despite the simplistic view that soft microenvironments are necessary to reduce scar formation, as in fetal wound healing, the increased signaling and cytoskeletal remodeling on HA gels indicate the importance of the modulation of contractile machinery of fibroblasts in wound repair, as discussed earlier in this section. Further investigation of this phenomenon via studies that take HA viscoelastic substrates into account is also warranted ( 210 ).…”
Section: Repair and Fibroblastsmentioning
confidence: 99%
“…5,8,10,24,25 Recent studies found that viscoelastic hydrogels supported reduced cell spreading and nuclear translocation of mechanoregulatory transcriptional factors as a result of lower cellular contractility compared to elastic hydrogels of similar stiffness. 26–33…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, natural ECM components have also been used to generate single component hydrogels that readily support cell attachment, but are more limited in the possibilities for tuning their biomechanical properties. Examples of such hydrogels include collagen type I, fibrin, gelatin (methacrylate) and hyaluronan ( Bourke et al, 2011 ; Tjin et al, 2017 ; Sun et al, 2020 ; Martinez-Garcia et al, 2021b ; Hui et al, 2021 ; Blokland et al, 2022 ; Loebel et al, 2022 ; Martinez-Garcia et al, 2022 ). Such hydrogels provide the 3D environment for cells, modelling the dimensionality and possibly the biomechanical mimicry of the in vivo situation, but they are not reflective of the complexity of the ECM components within the tissue microenvironment.…”
Section: Introductionmentioning
confidence: 99%